A method for preparing a three-dimensional carbonized conductive composite material
The three-dimensional structure is prepared by polyacrylonitrile spinning and pre-oxidation, braiding, electrophoresis and high-temperature carbonization treatment, which solves the problem of large changes in the conductivity of metal fiber conductive materials under bending and stress conditions, and realizes a high-strength and flexible three-dimensional carbonized conductive composite material, which is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411688040.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The conductivity of existing metal fiber conductive materials varies greatly under bending and stress conditions, limiting their application in flexible fabric sensing and wearable devices.
Three-dimensional structures were prepared by polyacrylonitrile spinning, pre-oxidation, braiding, electrophoresis treatment, and carbonization in nitrogen medium at high temperature to obtain three-dimensional carbonized conductive composite materials.
A three-dimensional carbonized conductive composite material that maintains good conductivity under bending and stress conditions is achieved, and is suitable for human motion detection, health monitoring and smart wearable textiles.
Smart Images

Figure CN119162713B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing a three-dimensional carbonized conductive composite material, and belongs to the technical field of conductive fibers. Background Art
[0002] At present, the research on common flexible conductive fabrics is mainly based on metal fibers. Although metal fibers have good conductive properties, they have disadvantages such as high density, poor chemical stability, high rigidity, and difficult processing. In particular, their conductive properties change greatly after being bent and deformed by external forces, which limits the wide application of metal fibers in flexible fabric sensing. Conductive materials based on textile fibers have many advantages, especially softness, comfort and wearability. The application fields of conductive materials have expanded to biology, aerospace, transportation, medical care, health care and other fields, and have broad development prospects. Summary of the invention
[0003] In view of this, the present application provides a method for preparing a three-dimensional carbonized conductive composite material, which can not only obtain a three-dimensional structure, high-strength, and flexible conductive composite material, but also can maintain good conductive properties under bending and stress conditions, and has good application prospects in human motion detection, body health monitoring, and smart wearable textiles.
[0004] Specifically, the present application is implemented through the following scheme:
[0005] A method for preparing a three-dimensional carbonized conductive composite material, using polyacrylonitrile as a raw material, electrospinning a spinning solution of polyacrylonitrile to obtain polyacrylonitrile filaments, pre-oxidizing the polyacrylonitrile filaments, weaving them into a three-dimensional structure, and then subjecting them to electrophoresis treatment and high-temperature carbonization treatment in a nitrogen medium to obtain a three-dimensional carbonized conductive composite material.
[0006] In the above scheme, the polyacrylonitrile spinning solution is electrospun to obtain polyacrylonitrile filaments, the polyacrylonitrile filaments are pre-oxidized and then woven into a three-dimensional structure, then electrophoretically treated, and finally treated at high temperature in a nitrogen medium to finally form a conductive composite material. The composite material obtained by the above method is high-strength and soft, and has excellent conductive properties in a flat or bent state, and has good application prospects in human motion detection, physical health monitoring, and smart wearable textiles.
[0007] Further, as a preference:
[0008] The polyacrylonitrile is added to N,N-dimethylformamide, stirred at 60-65°C until dissolved, and degassed to obtain a spinning solution of polyacrylonitrile, in which the content of polyacrylonitrile is 3-5%, and the content of N,N-dimethylformamide is 95-97%. Preferably, the polyacrylonitrile is stirred at 65°C until dissolved, and degassed to obtain a spinning solution of polyacrylonitrile, in which the content of polyacrylonitrile is 3%, and the content of N,N-dimethylformamide is 97%.
[0009] The electrospinning solution extrusion speed is 0.5-0.8 mL / h, and the voltage is 15-25 kV.
[0010] The pre-oxidation temperature is 200-280°C, and the pre-oxidation time is 1-2 hours. The polyacrylonitrile filament is placed in a tubular resistance furnace and pre-oxidized in an air medium. The pre-oxidation temperature can be increased from room temperature to 280°C, and the heating rate is 3°C / min.
[0011] In the electrophoresis process, the isopropanol dispersion of modified copper is used as the electrophoresis liquid, the carbonization product is used as the cathode, and graphite is used as the anode. Ultrasonic vibration is first performed for 30 to 60 minutes, and then electrodeposition is performed for 10 to 30 minutes.
[0012] Preferred:
[0013] In the isopropanol dispersion of modified copper, the mass percentage of modified copper in the dispersion is 1-5%.
[0014] Preparation method of modified copper: weigh sodium dodecyl sulfate and sodium dithionite in a four-necked flask, add deionized water and stir until uniform, and heat to 80°C, measure copper sulfate pentahydrate in a separatory funnel, and add all of them at a rate of 60 to 80 drops per minute. At this time, the content of copper sulfate pentahydrate is 2 to 10%, continue stirring and reacting for 2 to 3 hours, and filter to obtain modified copper particles. The particle size of the modified copper is preferably 800 to 5000 nm.
[0015] The voltage of the electrodeposition is 100-200V DC voltage.
[0016] The temperature of the high temperature carbonization treatment is 600-1200° C., and the carbonization time is 40-60 minutes. The three-dimensional structure obtained by weaving is treated at high temperature in a nitrogen medium. After completion, the carbon ash on the surface of the fabric is cleaned and removed, and the fabric is rolled and stored.
[0017] The three-dimensional carbonized conductive composite material prepared by the above method has excellent strength, flexibility and conductivity, and the conductivity changes little under the action of external force. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0019] Figure 1 This is an electron microscope image of the three-dimensional carbonized conductive composite material in this application;
[0020] Figure 2 This is the X-ray diffraction pattern of the three-dimensional carbonized conductive composite material in this application.
[0021] Figure 3 The graph is a graph showing the relationship between applied pressure and resistance change rate of the conductive composite material of the present application. DETAILED DESCRIPTION
[0022] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application clearer, the technical solutions in the embodiments of this application will be further described in detail below in conjunction with the drawings in the embodiments of this application. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit the technical solutions of this application. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0023] Example 1
[0024] This embodiment provides a method for preparing a three-dimensional carbonized conductive composite material, the steps of which are as follows:
[0025] (1) Preparation of spinning solution:
[0026] Weigh 1.5 g of polyacrylonitrile and put it into 82 g of N,N-dimethylformamide. Heat it in a water bath at 65°C with magnetic stirring for 6 h to fully dissolve the polyacrylonitrile. The magnetic stirring speed is fixed at 130 rpm. Then, ultrasonically disperse it at 30°C for 10 min. Degas the obtained spinning solution for later use.
[0027] (2) Electrospinning
[0028] The degassed spinning solution in step (1) is placed in an electrospinning device, and the electrospinning solution extrusion speed is controlled to be 0.5 mL / h and the voltage is 15 kV, and polyacrylonitrile fibers are spun.
[0029] (3) Pre-oxidation:
[0030] The polyacrylonitrile fiber was placed in a tubular resistance furnace and pre-oxidized in an air medium. The temperature was increased from room temperature to 280°C at a rate of 3°C / min and maintained for 2 hours to obtain polyacrylonitrile-based pre-oxidized yarn.
[0031] (4) Weaving process:
[0032] The pre-polyacrylonitrile filaments are woven using a fully automatic rapier loom, with a twist of 90 / cm, a deep cross-linked structure, and a yarn density of 100 strands / cm.
[0033] (5) Electrophoresis process:
[0034] The modified copper isopropanol dispersion was used as the electrophoresis liquid, the carbonization product was used as the cathode, and graphite was used as the anode. Ultrasonic vibration was first performed for 30 minutes, and then electrodeposition was performed for 10 minutes at a DC voltage of 100 V to obtain the finished product.
[0035] The mass percentage of modified copper in the electrophoresis solution is 2%.
[0036] Preparation method of modified copper: weigh 8.0g sodium dodecyl sulfate and 3.5g sodium dithionite in a four-necked flask, add deionized water and stir until uniform, stir at a speed of 500 rpm, and heat to 80°C, measure copper sulfate pentahydrate in a separatory funnel, add all at a speed of 60 drops per minute at 80°C, continue stirring and reacting for 2 hours, and filter to obtain modified copper particles. Among them, the mass percentage of copper sulfate pentahydrate relative to the total mass (sodium dodecyl sulfate, sodium dithionite, copper sulfate pentahydrate, deionized water) is 10%.
[0037] (6) High temperature treatment:
[0038] The pre-oxidized silk woven fabric was carbonized in a nitrogen medium at a carbonization temperature of 1000°C and a carbonization time of 60 min.
[0039] The finished product obtained by carbonization is a three-dimensional carbonized conductive composite material, and its SEM image is as follows: Figure 1 As shown: the surface of the carbonized conductive composite material has grooves and irregular particles deposited, indicating that the sample has certain surface activity and conductive properties.
[0040] The XRD patterns of carbonized conductive composite materials and commercially available carbon cloth are shown in Figure 2. Figure 2 As shown, it can be seen that the carbonized conductive composite material and the commercially available carbon cloth have graphite carbon diffraction peaks near 2θ=26.20°, and the diffraction peak intensity of the carbonized conductive composite material is higher, indicating that the degree of graphitization is improved. At the same time, the diffraction peaks of copper and its oxides appear near 2θ=41.50°.
[0041] The curve of applied pressure and sample resistivity is shown in Figure 3As shown in the figure, it can be seen that: under the condition of applied pressure, the resistivity of the carbonized conductive composite material changes little, and the resistivity is basically stable at about 5 mΩ·cm, indicating that the material has a relatively stable conductivity under the action of external force. However, the resistivity of commercially available carbon cloth changes greatly, and as the applied pressure increases, the resistivity increases significantly, reaching 40 mΩ·cm.
[0042] The performance of the finished product was tested, and the results are shown in Table 1.
[0043] Table 1: Performance comparison between the three-dimensional carbonized conductive composite material obtained in Example 1 and commercially available carbon cloth
[0044] .
[0045] Combination Figure 3 It can be seen from Table 1 that compared with commercially available carbon cloth, the three-dimensional carbonized conductive composite material prepared in the present application has excellent conductive properties and good softness.
[0046] Test method:
[0047] The resistivity of the sample characterizes its conductivity. The smaller the resistivity, the better the conductivity. The sample size is 20×25cm, the probe spacing is no more than 2mm, and the average value is taken after 3 measurements.
[0048] Sample breaking strength test: According to the national standard GB / T 3923.1-2013 "Tensile properties of textile fabrics - Part 1: Determination of breaking strength and elongation at break (strip method)", the test was carried out at a temperature of 20°±2℃ and a humidity of 60±2%.
[0049] The softness of the sample is characterized by stiffness. The bending stiffness and bending length of the fabric directly reflect the softness of the fabric. The smaller the bending stiffness, the easier the fabric is to bend, indicating that the softer it is. Refer to GB / T18318.1-2009 "Determination of Flexural Properties of Textiles Part 1: Inclined Plane Method" for testing.
[0050] The change of resistivity of the sample under external force is determined by the pressure-sensitive test. In the pressure-sensitive test, a regular tetrahedral indenter is pressed into the sample surface with different forces, held for 30 seconds, and then the change of the sample resistivity and the applied pressure is measured.
[0051] Example 2: Effect of yarn density
[0052] The configuration of this embodiment is the same as that of embodiment 1, except that the yarn density is as shown in Table 2.
[0053] Table 2: Effect of yarn density on the properties of finished three-dimensional carbonized conductive composites
[0054] .
[0055] It can be seen from Table 2 that with the increase of yarn density, the resistivity of the three-dimensional carbonized conductive composite material continues to decrease, the conductive performance continues to improve, and the softness decreases slightly. This is mainly because the more yarns per unit length, the greater the weaving density, which reduces the porosity of the fabric, increases the thickness, and increases the number of yarn intersections, so the conductive performance is improved.
[0056] Example 3: Effect of electrophoresis fluid composition
[0057] The configuration of this embodiment is the same as that of embodiment 1, except that in step (5), the components of the electrophoretic solution are modified copper, copper sulfate, copper chloride and copper nitrate, respectively. The influence of the components of the electrophoretic solution on the performance of the finished three-dimensional carbonized conductive composite material is discussed, and the results are shown in Table 3.
[0058] Table 3: Effect of electrophoretic fluid composition on the properties of finished three-dimensional carbonized conductive composite materials
[0059] .
[0060] When modified copper is used as electrophoresis liquid, the guiding performance of the three-dimensional carbonized conductive composite material is better than that of copper sulfate, copper chloride and copper nitrate. This is mainly because the modified copper contains some active sulfonic acid groups and hydroxyl groups, and the grooves on the surface of the sample after carbonization are easy to react with the active groups in the modified copper, so the conductive performance is better.
[0061] Example 4: Effect of modified copper concentration
[0062] The configuration of this embodiment is the same as that of embodiment 1, except that the mass fractions of nano copper are 1%, 1.5%, 2%, 2.5%, and 3%, respectively. The effect of the mass fraction of modified copper on the performance of the finished three-dimensional carbonized conductive composite material is discussed, as shown in Table 4.
[0063] Table 4: Effect of modified copper mass fraction on the properties of finished three-dimensional carbonized conductive composites
[0064] .
[0065] As the mass fraction of modified copper increases, the conductivity of the three-dimensional carbonized conductive composite material continues to improve. However, when the mass of modified copper exceeds 2.5%, the strength of the three-dimensional carbonized conductive composite material decreases slightly. This may be because more metal copper is deposited on the surface of the composite material after electrophoresis, which affects the sliding of its fibers and affects its strength.
[0066] Example 5: Effect of high temperature treatment temperature
[0067] The configuration of this embodiment is the same as that of embodiment 1, except that in step (6), the temperature is set to 600, 800, 900, 1000, and 1200, respectively. The effect of temperature on the performance of the finished three-dimensional carbonized conductive composite material is discussed, and the results are shown in Table 5.
[0068] Table 5: Effect of processing temperature on the properties of finished three-dimensional carbonized conductive composites
[0069] .
[0070] As the treatment temperature increases, the conductivity of the three-dimensional carbonized conductive composite material continues to improve, and the softness decreases slightly. This is mainly because the high temperature treatment increases the degree of graphitization of the sample, thereby improving the conductivity. After the carbonization temperature is stable above 1000℃, the softness of the three-dimensional carbonized conductive composite material deteriorates.
[0071] The above-mentioned embodiments only express several feasible implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention, and the embodiments are not used to limit the scope of protection in the claims of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and all equivalent implementations or changes that do not depart from the present invention should be included in the technology of the present invention.
Claims
1. A method for preparing a three-dimensional carbonized conductive composite material, characterized in that: Using polyacrylonitrile as raw material, the spinning solution of polyacrylonitrile is electrospun to obtain polyacrylonitrile filaments. After pre-oxidation, the polyacrylonitrile filaments are woven into a three-dimensional structure. After electrophoresis, they are carbonized in a nitrogen medium to obtain a three-dimensional carbonized conductive composite material. The pre-oxidation temperature is 200-280° C., and the pre-oxidation time is 1-2 hours; The weaving adopts a fully automatic rapier loom, with a twist of 90 / cm, a deep cross-linked structure, and a yarn density of 60 to 110 strands / cm. In the electrophoresis process, the modified copper isopropanol dispersion is used as the electrophoresis liquid, ultrasonically vibrated for 30 to 60 minutes, and then electrodeposited for 10 to 30 minutes at a DC voltage of 100 to 200 V. In the isopropanol dispersion of modified copper, the mass percentage of modified copper is 1-3%. The modified copper preparation method comprises: weighing sodium dodecyl sulfate and sodium dithionite, adding deionized water and stirring evenly, heating to 80° C., dripping copper sulfate pentahydrate at a rate of 60 to 80 drops / min until the content of copper sulfate pentahydrate is 2 to 10%, and continuing to stir the reaction after the dripping is completed, filtering to obtain modified copper particles. The temperature of the carbonization treatment is 600-1200° C., and the treatment time is 40-60 minutes.
2. The method for preparing a three-dimensional carbonized conductive composite material according to claim 1, characterized in that: The polyacrylonitrile is added to N,N-dimethylformamide, stirred at 60-65° C. until dissolved, and degassed to obtain a polyacrylonitrile spinning solution, in which the content of polyacrylonitrile is 3-5%, and the content of N,N-dimethylformamide is 95-97%.
3. The method for preparing a three-dimensional carbonized conductive composite material according to claim 1, characterized in that: The electrospinning solution extrusion speed is 0.5-0.8 mL / h, and the voltage is 15-25 kV.
Citation Information
Patent Citations
Preparation method for polyacrylonitrile-based carbon cloth
CN102704227A
Preparation method of high-conductivity high-strength copper-plated carbon fiber
CN115821340A